KEMAMPUAN MEMBACA PEMAHAMAN TEKS EKSPOSISI SISWA KELAS VII SMPN 02 SIAK HULU KABUPATEN KAMPAR - Novriani, Reza; ', Auzar; Hakim, Nursal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: this research is a study about the ability on reading comprehension in Exposition text of the first year students of SMPN 02 Siak Hulu, Kampar. This research aimed to know and describe the ability on reading comprehension in Exposition text of the first year students of SMPN 02 Siak Hulu, Kampar. This research was quantitative descriptive. The data of this research was the results of the reading comprehension in narrative text test (answers) of the first year students of SMPN 02 Siak Hulu, Kampar. The form of the instrument in this research was multiple choices which have four possible answers that related with the ability on reading comprehension in Narrative text of the first year students of SMPN 02 Siak Hulu, Kampar. The data collecting technique was taken by test technique. The total of the population in this research was 139 and determined to 103. The data was analyzed by quantitative. The validity was gotten by the data validation. The result of this research was sighted from the result of reading comprehension test of the first year students of SMPN 02 Siak Hulu, Kampar. Based on the ability on reading comprehension in Narrative text of the first year students of SMPN 02 Siak Hulu, Kampar was in very low category with the average score 44.Key words: Ability, Reading Comprehension, Exposition Text.